Anterior Cruciate Ligament Reconstruction and Lateral Plasty in High-Risk Young Adolescents: Revisions, Subjective Evaluation, and the Role of Surgical Timing on Meniscal Preservation. (March 2022) - Grassi, Alberto; Macchiarola, Luca; Lucidi, Gian Andrea; Dal Fabbro, Giacomo; Mosca, Massimilano; Caravelli, Silvio; Zaffagnini, Stefano
Background: In adolescents, the rate of meniscal injury at the time of anterior cruciate ligament (ACL) reconstruction, the rate of ACL graft revision, and clinical outcomes has not yet been investigated. Hypothesis: In patients younger than 16 years, the rate of meniscal injuries at the time of ACL reconstruction increases with time from injury. The mid-term revision rate and reoperation rate after ACL reconstruction with hamstrings and lateral tenodesis are lower than those reported in literature for isolate ACL reconstruction. Study Design: Case series. Level of Evidence: Level 4. Methods: Patients younger than 16 years who underwent ACL reconstruction with hamstring and lateral tenodesis, with a follow-up ≥2 years were included. The number of meniscal lesions was stratified according to the delay between injury-to-surgery (<3, 3-12, >12 months). All reoperations, Lysholm score, Knee Injury and Osteoarthritis Outcome Score subscales for pain (at rest and during activity), and return to sport were collected. Results: A total of 151 patients (mean age 14.8 ± 1.2 years) were included. Patients undergoing surgery at <3 months after injury had a lower meniscal injury rate (36%) than those treated at 3 to 12 months (55%) and >12 months (63%) after injury ( P = 0.04). Medial meniscal lesions were more likely to be repaired when surgery was performed <3 months after injury (91%). Subjective follow-up data were available for 132 patients, and 19 were lost to follow-up. At 6.0 ± 2.6 years, 6% of patients underwent ACL revision; 1 of 20 (5%) patients with posterior tibial slope ≥12° and 4 of 45 (9%) patients with Tegner level ≥8. Nine new meniscal procedures were performed; 19% of repaired menisci underwent meniscectomy. Good or excellent Lysholm score was reported by 88% of patients; 56% of patients with concurrent lateral meniscectomy had pain during activity, 91% returned to sport, and 79% were still participating at final follow-up. Conclusion: Patients younger than 16 years undergoing ACL reconstruction within 3 months from injury had the lowest rate of meniscal injuries. ACL reconstruction with lateral tenodesis had low revision rate (6%) and good or excellent clinical outcomes in 88% of young adolescents. Clinical Relevance: Sport physicians should be aware that adolescent patients undergoing ACL reconstruction within 3 months after injury have the lowest rate of meniscal injuries; the mid-term revision rate of ACL reconstruction with lateral plasty is lower than 10% and the patients' perceived outcomes are good with almost all patients returning to sport activity.